Fiscal decentralization influence on public services efficiency and economic growth - Kaneva, Tetiana; Karpenko, Maksym; Nasibova, O.; Tabenska, Julia; Tomniuk, Tetiana (ТОВ " Фінтехальянс ", 2023)
Theoretically, fiscal decentralization is associated with growing up in the public administration's efficiency and fostering economic growth. But the mentioned things depend on numerous factors and strongly differ from country to country. This article aims to assess the efficiency of public services, provided by local governments, determine the role of fiscal decentralization in this process, and evaluate the fiscal decentralization impact on economic growth. We found that the highest level of public service quality was demonstrated in Estonia and Slovenia among the 15 counties of Central and Eastern Europe. There was no evidence that fiscal ecentralization had strong interconnections with the efficiency of public services. The results showed that revenue ecentralization harms the GDP per capita growth and expenditure decentralization has only a tiny pos itive impact on economic growth in Central and Eastern Europe over the 2010-2022 period. The authors concluded that the efficiency of the local budget's expenditures should be increased, cause the enhancement of the public expenditures-to-GDP ratio would have adverse effects without institutional improvement.

Теоретичні дослідження вказують, що фіскальна децентралізація пов’язана з підвищенням ефективності державного управління та сприяє процесам економічного зростання. Водночас згадані речі залежать від багатьох факторів і дуже відрізняються в розрізі країн. Метою дослідження є оцінка ефективності суспільних послуг, що їх надають органи місцевого самоврядування; визначення ролі фіскальної децентралізації в цьому процесі та оцінювання впливу фіскальної децентралізації на економічне зростання. Авторами виявлено, що серед 15 країн Центральної та Східної Європи найвищий рівень якості публічних послуг зафіксовано в Естонії та Словенії. Не знайдено очевидних доказів того, що фіскальна децентралізація має тісний взаємозв’язок із ефективністю надання суспільних послуг. Результати дослідження засвідчили, що децентралізація в царині доходів стримує зростання реального ВВП на одну особу, а децентралізація в царині видатків має лише незначний позитивний вплив на економічне зростання в Центральній та Східній Європі протягом періоду 2010-2022 років. Автори дійшли висновку, що ефективність видатків місцевих бюджетів слід підвищувати, оскільки просте зростання співвідношення державних видатків до ВВП може мати негативні наслідки без інституційного вдосконалення.
Вплив фіскальної децентралізації на ефективність суспільних послуг та економічне зростання
Keywords: fiscal decentralization; local governments; budget expenditures; public services; efficiency of public services; economic growth; фіскальна децентралізація; органи місцевого самоврядування; видатки бюджету; суспільні послуги; ефективність; економічне зростання